INFEKSI KLEBSIELLA OXYTOCA PADA PRIA DENGAN KOLITIS ULSERATIF - Mutiara Ferina; Pusparini Pusparini; Alvina Alvina (Jurnal Akta Trimedika, 2025)
Ulcerative colitis is one of the types of Inflammatory Bowel Disease (IBD), in addition to Crohn's disease. Ulcerative colitis is a chronic inflammatory disease that affects the colon and rectum. The predominant age of patients is between 15 and 30 years, with a second peak occurring between 60 and 80 years of age. In ulcerative colitis, there is an increased incidence of infections compared to non-ulcerative colitis patients. This case presents a 47-year-old male with ulcerative colitis who has been experiencing bloody stools for 2 weeks. Stool culture results identified an isolate of Klebsiella oxytoca.